Unemployment and Persistent Poverty in the Niger Delta Region of Nigeria: A Constraint to Sustainable Development in the 21st Century Nigeria - Inyang, Bassey; Simon, E.D. (Mediterranean Journal of Social Sciences, 2012)
This paper examines the phenomenon of unemployment and persistent poverty in Nigeria with special reference tothe Niger Delta region. Having diagnosed the episode of unemployment and poverty in the region, the paper unfolds thatunemployment and poverty have devastating effect on individuals, society and economy at large. This paper identifies that oneof the core causes of poverty in the Niger Delta today is the inability of many job seekers to secure gainful employment. It alsoreveals the increasing level of poverty which has conditioned many people to a very low and undignified standard of living in theregion. The paper identifies unemployment and poverty as impacting negatively on the lives of the people and sustainabledevelopment programmes in the region. Economic growth, which is supposed to be a solution to the problem of unemploymentand poverty, appears not to be in this region. In view of this, the paper recommends that the government and all stake-holdersmust work together to get over the hurdles of unemployment and poverty and create more poverty alleviation programmes inorder to promote maximum investment and employment opportunity to the rural dwellers for sustainable development at the ruralsetting.